2009
DOI: 10.1177/0269881108100777
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of antipsychotic dosage and polypharmacy: a study with the BACS in patients with schizophrenia and schizoaffective disorder

Abstract: Antipsychotic polypharmacy and high doses have been associated with poorer outcome, longer hospital stays, and increased side effects. The present naturalistic study assessed the cognitive effects of antipsychotics in 56 patients with a diagnosis of schizophrenia or schizoaffective disorder, using the Brief Assessment of Cognition in Schizophrenia (BACS). Antipsychotic daily dose (ADD) was expressed as mg risperidone equivalents/day (RIS eq), using a model based on drug doses from the Clinical Antipsychotic Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 45 publications
3
90
2
1
Order By: Relevance
“…[100][101][102][103][104][105][106][107] Other studies have not replicated these findings. 108 These data do not address the risk of short-term use of antipsychotics to manage delirium and cannot be extrapolated to this situation.…”
Section: Irwin Et Almentioning
confidence: 99%
“…[100][101][102][103][104][105][106][107] Other studies have not replicated these findings. 108 These data do not address the risk of short-term use of antipsychotics to manage delirium and cannot be extrapolated to this situation.…”
Section: Irwin Et Almentioning
confidence: 99%
“…16 Other evidence suggests antipsychotic polypharmacy increases time in hospital 17 and decreases cognitive performance. 18 There is more contentious evidence that polypharmacy increases the risk of metabolic disturbances. [19][20][21][22] Worryingly, this apparently dangerous and poorly supported practice may be more common in Black and minority ethnic patients than in White patients.…”
Section: Editorialmentioning
confidence: 99%
“…[3][4][5]9,10 In addition, there is evidence for harm associated with APP. Research has shown an association of APP with increased adverse effects, including extrapyramidal effects, [11][12][13] hyperprolactinemia, [14][15][16] sexual dysfunction, 17 hypersalivation, 18 sedation, 14 cognitive impairment, 19 and diabetes. 20,21 Possible increased risk of sudden cardiac death 22 and mortality 23,24 has been suggested.…”
Section: Introductionmentioning
confidence: 99%